Modelo de decisão sobre os fatores de risco para internação por pneumonia em lactentes: estudo caso-controle em um hospital de referência no município de João Pessoa - Soares, Maria Elma de Souza Maciel (2011)
Respiratory diseases in childhood, particularly pneumonia, are a serious public health problem, since they are directly related to morbidity and mortality of children in Brazil and worldwide. World Health Organization data show that the annual incidence of pneumonia is 156 million new cases, of which 151 million occur in developing countries. Of these, 20 million require hospitalization because of the gravity. This study aims to identify risk factors associated with hospitalization for pneumonia in children between 0 and 2 years old, as well as build a decision model that can explain the occurrence of pneumonia in this age group. This is a case-control study conducted in a referral hospital in João Pessoa PB. The study included 186 children 60 pneumonia cases and 126 controls. We used the chi-square test, and then multivariate analysis using logistic regression model. In the chi-square test, the following variables were considered significant: maternal age, type of delivery, birth weight, breastfeeding, parity, previous hospitalization, reason for hospitalization, vaccination, child care, overcrowding, access to sewage treatment, health unit, type of household and maternal education. In the final decision model, were considered significant the variables previous hospitalization and maternal education as risk factors, and access to vaccination and treatment of sewage as protective factors. These study results corroborate previous studies and provide information for health managers to develop intervention programs on these factors with the aim of reducing morbidity due to pneumonia in children.